Analisis Rencana Implementasi Metode EOG Terhadap Manajemen Persediaan Barang pada Pabrik Beras Giri Jaya Putra - Faiz, Muhammad Akmal Rizki; Hidayat, Abdul Anhar; Maharani, Alya; Sari, Uci Permata; Suherman, Ujang (CV. Lenggogeni Data Publishing, 2024)
The inventory of raw materials or materials at PB Giri Jaya Putra is not well planned, so the raw materials run out during the production process. The company also does not pay attention to the quantity and reorder point of raw materials. Thus, costs that should not be needed increase, which means that they are not effective and efficient. As a result, PB Giri Jaya Putra decided to apply the quantity demand economics method in raw material management. The purpose of this study is to find out how the application of the quantity demand economic method (EOQ) in raw material stock management in PB Giri Jaya Putra. This research uses quantitative methods with the object of research in PB Giri Jaya Putra. The company's inventory data from 2022-2023 was used as a research sample, which was taken by purposive sampling method. The results showed that the cost has decreased by 59% from by saving Rp. 20,213,212.95. The results showed that the EOQ method played a significant role in controlling the availability of raw materials in PB Giri Jaya Putra.